2002
DOI: 10.1088/0965-0393/10/2/307
|View full text |Cite
|
Sign up to set email alerts
|

Instability of hcp structures in modified embedded atom method

Abstract: By performing isobaric-isothermal molecular dynamics simulations for Ti we have obtained the result that the `modified embedded atom method' potential creates stable structures different from the hcp structure, with a non-ideal c/a ratio that is experimentally stable. The hcp-to-bcc transformation at high temperature is reproduced. However, attempts to make the hcp structure the ground state structure, by adjusting the many-body screening function or by taking the second-nearest neighbour interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Hence, this potential is unsuitable for our contact simulations. While modified embedded atom method (MEAM) potentials 23,24 have significantly more flexibility, the MEAM potentials fail to produce a stable hcp crystal, as noted previously by Mae et al 25 . We confirmed this via MD simulations, which showed that application of a small strain destabilized the hexagonal close packed lattice of MEAM Ru.…”
Section: Interatomic Potentialsmentioning
confidence: 75%
“…Hence, this potential is unsuitable for our contact simulations. While modified embedded atom method (MEAM) potentials 23,24 have significantly more flexibility, the MEAM potentials fail to produce a stable hcp crystal, as noted previously by Mae et al 25 . We confirmed this via MD simulations, which showed that application of a small strain destabilized the hexagonal close packed lattice of MEAM Ru.…”
Section: Interatomic Potentialsmentioning
confidence: 75%
“…We believe that this is related to a small energy difference between hcp and fcc structures in our MEAM potential for Mg (see Fig. 2) and instability of hcp structures in MEAM 45 . Further detailed investigation of this subject is beyond the scope of the present work and will be reported in separate papers.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 86%
“…Interface Dataset (II) further includes the data points reflecting those of Ru and SiO 2 -slab models as surface structures which are non-interface structures. We also prepared interface test sets including the data points of the SiO 2 /Ru/SiO 2 stacking structures with Ru[0001]/SiO 2 and Ru [11][12][13][14][15][16][17][18][19][20]/SiO 2 interfaces. Each interface test set includes 33 data points.…”
Section: Training Datasetmentioning
confidence: 99%
“…14) The first step in performing MD simulations is to develop interatomic potential. Empirical interatomic potentials for interconnect metals have already been developed in terms of Finnis-Sinclair (FS) type potential for Ru, 15) embedded atom method (EAM) type potential for Ru, 16) modified EAM (MEAM) type potential for Ru, 17) analytical bond-order potential for several covalent materials with Ru, 18) and charge-optimized many-body potential for the Cu/a-SiO 2 interface. 19) However, these empirical interatomic potentials may not adequately represent Ru/ILD interfaces with interlayers, due to their poor adaptability caused by the significant costs of parametrizing potential parameters for multi-element mixed systems.…”
Section: Introductionmentioning
confidence: 99%